2017
DOI: 10.1097/mao.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Changes After Intratympanically Applied Steroids for Primary Therapy of Sudden Hearing Loss: A Meta-analysis Using Mathematical Simulations of Drug Delivery Protocols

Abstract: Objective Controlled and uncontrolled studies with primary intratympanic (IT) or combined intratympanic and systemic application of glucocorticosteroids for idiopathic sudden hearing loss (ISSHL) were analyzed by means of a meta-analysis in an attempt to establish optimal local drug delivery protocols. Study Design A total of 25 studies with 28 treatment groups between January 2000 and June 2014 were selected that adequately described drug delivery protocols. Cochlear drug levels were calculated by a validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 79 publications
(64 reference statements)
4
52
1
8
Order By: Relevance
“…162 However, a meta-analysis with mathematical simulations of the various IT protocols used in these studies as well as others showed that the trend of early treatment having a positive effect on hearing is likely a ''sham effect'' due to spontaneous recovery. 163 The mathematical model accounted for the variability in drug used, concentration, application time, number of injections, frequency of injections, and duration of treatment in addition to patient's pre-and posttreatment PTAs. The authors concluded that the final hearing did not depend on the drug given, dose used, dosing frequency, or duration of treatment but rather on the severity of the hearing loss.…”
Section: Systemic Steroids Vs Placebo a Cochrane Review First Publimentioning
confidence: 99%
“…162 However, a meta-analysis with mathematical simulations of the various IT protocols used in these studies as well as others showed that the trend of early treatment having a positive effect on hearing is likely a ''sham effect'' due to spontaneous recovery. 163 The mathematical model accounted for the variability in drug used, concentration, application time, number of injections, frequency of injections, and duration of treatment in addition to patient's pre-and posttreatment PTAs. The authors concluded that the final hearing did not depend on the drug given, dose used, dosing frequency, or duration of treatment but rather on the severity of the hearing loss.…”
Section: Systemic Steroids Vs Placebo a Cochrane Review First Publimentioning
confidence: 99%
“…From the pharmacokinetic view, intracochlear drug concentrations are dependent on the area and time the drug is in contact with the RWM [Liebau et al, 2017]. It is reported that the longest diam- eter of the RW was from 1.32 to 2.35 mm (mean 1.90 mm) [Atturo et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion coefficient of methylprednisolone is 0.784 × 10 -9 m 2 /s [Plontke et al, 2008], higher than that of dexamethasone, which is 0.77 × 10 -9 m 2 /s [Salt et al, 2011], which indicates that methylprednisolone permeates into the perilymph via the RWM faster. Second, as for perilymph elimination half-time, that of methylprednisolone is 27 min, and dexamethasone is eliminated much faster with 22.5 min [Liebau et al, 2017]. Third, methylprednisolone can also regulate sodium transport or/and reabsorption in the cochlea, which is important for inner ear function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch einige systematische Übersichtsarbeiten und Metaanalysen befassten sich mit den verschiedenen Therapiestrategien der intratympanalen Hörsturztherapie mit Kortikosteroiden [110][111][112][113][114][115][116][117]. Aufgrund der oben erwähnten Qualitätsmängel, der unterschiedlichen verwendeten Medikamente (z.…”
Section: Hörsturztherapie Mit Kortikosteroidenunclassified